Mitochondrial genome of Lipaphis pseudobrassicae (Davis, 1914) and phylogenetic analysis of Aphidinae - LIN Xingyu; SONG Nan (浙江大学学报. 农业与生命科学版, 2024)
Lipaphis pseudobrassicae (Davis, 1914) is an important agricultural insect pest. In this study, we sequenced and analyzed the entire mitochondrial genome of L. pseudobrassicae, and reconstructed the phylogenetic relationships of Aphidinae based on the mitochondrial genome data. In phylogenetic analyses, the ingroup included 31 species of Aphidinae, while the outgroup selected three species of Eriosomatinae (Eriosoma lanigerum, Paracolopha morrisoni and Meitanaphis microgallis). The maximum likelihood method and Bayesian method were used to reconstruct the phylogenetic tree of Aphidinae, respectively. The results showed that the mitochondrial genome of L. pseudobrassicae was 16 743 bp in length (GenBank accession No. OP796483), which contained 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes and one non-coding control region. The phylogenetic tree constructed by the maximum likelihood method and Bayesian method both showed that the tribe Aphidini was a monophyletic group. The tribe Macrosiphini was recovered as a monophyletic group, and Lipaphis was a sister to Brevicoryne according to the maximum likelihood method. However, the tribe Macrosiphini was recovered as a non-monophyletic group, and Lipaphis was a sister to Brevicoryne+Diuraphis according to the Bayesian method. This study can enhance the understanding of the phylogenetic relationships among Macrosiphini, Lipaphis, and L. pseudobrassicae by utilizing mitochondrial genome data.